Real-world study of the leakage of two types of infusion bags in multicenter pharmacy intravenous admixture service (PIVAS) - Yin, Yanchao; Fu, Wei; Liu, Wenhua; Li, Feie; Gong, Xuepeng; Liu, Dong; Li, Juan (Frontiers in Pharmacology, 2023)
Background: This study sought to analyze the leakage rate, economic loss caused by leakage, leakage reasons, and usage of upright polypropylene infusion bags and non-polyvinyl chloride (PVC) infusion bags, two types of closed intravenous infusion containers used in pharmacy intravenous admixture services (PIVAS), to improve the product quality of drug infusion packaging materials, reduce drug and clinical economic losses, and reduce the safety hazards of medication.A real-world study was used to collect statistics for these infusion containers.The study was conducted in 21 hospitals in China from September to December 2022.Upright polypropylene infusion bags or non-PVC infusion bags in PIVAS of these 21 hospitals were chosen as the research material.Results: In total, 2,349,899 upright polypropylene infusion bags and 3,301,722 non-PVC infusion bags were collected. Eleven cases of upright polypropylene infusion bag leakage occurred (with a the leakage rate of 0.05‱), and 394 cases of non-PVC infusion bag leakage occurred (with a leakage rate of 1.19‱). The leakage rate of non-PVC infusion bags was significantly higher than that of upright polypropylene infusion bags (P<0.01). The main reason for leakage in upright polypropylene infusion bags was sharp objects such as glass fragments or aluminum caps piercing the bag. The main reason for leakage in non-PVC infusion bags was squeezing, stacking, and uneven arrangement that causes folding of edges. For non-PVC bags, additional reasons for leakage included leakage at the nozzle joint, excessive manual or machine throwing force, and excessive dosage. The economic loss of upright polypropylene infusion bags was 1,116.56 CNY. The economic loss of non-PVC infusion bags was 32,210.86 CNY.Based on real-world study data on the leakage of upright polypropylene infusion bags and non-PVC infusion bags in multicenter PIVAS, it can be concluded that the leakage rates of upright polypropylene infusion bags are significantly lower than those of non-PVC infusion bags in PIVAS, and the economic losses due to upright polypropylene infusion bags are lower than those due to non-PVC infusion bags in PIVAS. Therefore, we can infer that upright polypropylene infusion bags are superior to non-PVC infusion bags.